2019
DOI: 10.1589/jpts.31.807
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of age-related changes in blood pressure, oxyhemoglobin saturation, and physique in Bolivians residing at different altitudes: presentation of basic data for health promotion

Abstract: [Purpose] To present basic data for a health promotion plan tailored to the body function of Bolivians residing in different municipalities and altitudes by investigating their blood pressure and oxyhemoglobin saturation. [Participants and Methods] The participants were 589 Bolivians residing in different altitudes who voluntarily participated in health promotion activities. We measured the blood pressure, peripheral capillary oxygen saturation, height, and weight, and calculated the body mass index. We divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…In our study the presence and severity of CMS were not associated with significant differences in ambulatory BP, either during daytime or during night-time. While a number of studies documented BP increase, in particular at night, during acute HA exposure [ 18 ], the evidence on systemic BP and arterial hypertension in highlanders is limited [ 19 , 20 , 30 ]. A meta-regression analysis of studies in Tibetan highlanders indicated a possible trend towards higher BP values with increasing altitude [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study the presence and severity of CMS were not associated with significant differences in ambulatory BP, either during daytime or during night-time. While a number of studies documented BP increase, in particular at night, during acute HA exposure [ 18 ], the evidence on systemic BP and arterial hypertension in highlanders is limited [ 19 , 20 , 30 ]. A meta-regression analysis of studies in Tibetan highlanders indicated a possible trend towards higher BP values with increasing altitude [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased night-time blood pressure (BP) has been specifically reported after acute exposure to high-altitude [ 18 ]. Although a direct linear association between altitude and BP has been suggested under prolonged altitude exposure [ 19 , 20 ], data are still limited. The mechanisms involved in the increased BP after hypoxic exposure include an increase in sympathetically-mediated vascular modulation, impaired endothelial function and an increase in blood viscosity due to haemoconcentration [ 21–23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Так, накоплен обширный научный материал, свидетельствующий о том, что длительное проживание человека в экстремальной среде высокогорья вызывает в организме жителей высокогорья глубокие энергетические, метаболические, физиологические и эндокринные перестройки [Барбашова, 1960;Бернштейн, 1967;Ахмедов, 1971;Турусбеков, 1971;Миррахимов, 1968Васильев с соавт., 1974;Исабаева, 1975;Данияров, 1979;Турусбеков с соавт, 1979;Калюжный, Белекова, 1982;Панин, 1983;Шорин, Лепеллеуто, 1986;Айдаралиев, Максимов, 1988;Коган, 1990;Агаджанян, 1994;Бец, 2000, Степанова, 2001Мукашева, 2004;Садыкова, Джунусова, 2016;Бесланев с соавт., 2017;Джунусова с соавт., 2017;Guerra-Garcia et al, 1965, цит. по: Клегг, 1981Sobrevilla et al, 1968Sobrevilla et al, , 1971Fiori et al, 1998;Zielinґski et al, 2000;Johnson et al, 2010;Shimura, Kubo, 2019].…”
Section: таблица 2 основные оценки статистических параметров изменчивости размерных признаков у киргизов памираunclassified
“…However, there are few studies from medical rehabilitation professionals, such as physical therapists, occupational therapists, or speech therapists, associated with interest in overseas volunteer participation (OVP). These studies were reported by the Japan Overseas Cooperation Volunteers in the Japan International Cooperation Agency (JICA) 5 , 6 ) .…”
Section: Introductionmentioning
confidence: 96%